N6-Methyladenosine Level in Silkworm Midgut/Ovary Cell Line Is Associated With Bombyx mori Nucleopolyhedrovirus Infection - Zhang, Xing; Zhang, Yunshan; Dai, Kun; Liang, Zi; Zhu, Min; Pan, Jun; Zhang, Mingtian; Yan, Bingyu; Zhu, Hanxue; Zhang, Ziyao; Dai, Yaping; Cao, Manman; et al. (Frontiers in Microbiology, 2020)
Bombyx mori nucleopolyhedrovirus (BmNPV) is one of the most serious pathogens in sericulture and causes huge economic loss annually. The roles of N6-methyladenosine (m6A) modification in silkworms following BmNPV infection are currently unclear. Here, methylated RNA immunoprecipitation with next-generation sequencing were applied to investigate the m6A profiles in silkworm midgut following BmNPV infection. A total of 9144 and 7384 m6A peaks were identified from the BmNPV-infected (TEST) and uninfected silkworm midguts (CON), respectively, which were distributed predominantly near stop codons. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of common m6A peaks in nuclear genes revealed that these m6A-related transcripts were associated with crucial signaling pathways. Comparative transcriptome analysis showed that 1221 differential expressed m6A peaks were identified between TEST and CON, indicating that m6A modification is regulated following BmNPV infection. GO and KEGG pathway analysis of the differentially expressed m6A peaks showed their association with signal transduction, translation and degradation. To understand further the effect of the m6A machinery on virus infection, expression levels of m6A-related genes were altered in silencing and overexpression experiments. Expression of viral structural protein VP39 was increased in BmN cells by siRNA-mediated depletion of methyltransferase-like (METTL) enzyme genes (BmMETTL3, BmMETTL14) and cytoplasmic YTH-domain family 3 (BmYTHDF3), while the reverse results were found after overexpression of the m6A-related enzymes in BmN cells. Overall, m6A modification might be a novel epigenetic mechanism that regulation BmNPV infection and interference with this mechanism may provide a novel antiviral strategy for preventing BmNPV disease.